2022
DOI: 10.1038/s41467-022-34994-z
|View full text |Cite
|
Sign up to set email alerts
|

Extensive germline-somatic interplay contributes to prostate cancer progression through HNF1B co-option of TMPRSS2-ERG

Abstract: Genome-wide association studies have identified 270 loci conferring risk for prostate cancer (PCa), yet the underlying biology and clinical impact remain to be investigated. Here we observe an enrichment of transcription factor genes including HNF1B within PCa risk-associated regions. While focused on the 17q12/HNF1B locus, we find a strong eQTL for HNF1B and multiple potential causal variants involved in the regulation of HNF1B expression in PCa. An unbiased genome-wide co-expression analysis reveals PCa-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…One potential issue of this study is inconsistent results in some tests among different cell lines. While these inconsistence may attribute to genetic heterogeneity, we also want to highlight that some candidates found exclusively in DU145 cells are reported to be functional in prostate cells (40). Additionally, to increase our gRNA library coverage, we may use a novel CRISPR systems with expanded PAM site compatibility.…”
Section: Discussionmentioning
confidence: 99%
“…One potential issue of this study is inconsistent results in some tests among different cell lines. While these inconsistence may attribute to genetic heterogeneity, we also want to highlight that some candidates found exclusively in DU145 cells are reported to be functional in prostate cells (40). Additionally, to increase our gRNA library coverage, we may use a novel CRISPR systems with expanded PAM site compatibility.…”
Section: Discussionmentioning
confidence: 99%
“…To discover the susceptibility loci for PCa, many GWAS projects have been initiated since 2005 and over 270 risk loci have been reported [ 35 37 ]. By investigating the molecular mechanisms underlying the biological effect of these risk SNPs, previous studies including ours suggest that these SNPs may affect gene regulation by modulating the binding of key transcription factors such as HOXB13, AR, and the most frequent PCa-specific fusion protein TMPRSS2-ERG [ 40 , 41 , 103 ] as well as the influence of genetic variants on transcription factor DNA-binding in other types of diseases [ 89 , 104 ]. One of our pioneer studies demonstrates that the PCa risk-associated allele at rs339331 impacts PCa predisposition and progression by altering RFX6 expression through a functional interplay with the PCa susceptibility gene HOXB13 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that genetic alterations play a crucial role in driving the progression of normal cells from the hyperplastic and dysplastic stages to metastatic disease, including invasive cancer. [31,32] Therefore, the analysis of gene alterations is essential for gaining novel insights into the role of oncogenes in cancer development. [33] In line with this, we investigated the muta- tion types of GSC across various cancers and observed that missense mutations were the most frequently occurring mutation type in multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%